HPV vaccination coverage in women between 15 and 55 years old in Spain: Temporal trend during the period 2007–2020. Issue 3 (7th January 2022) - Ramírez, Mar; de la Fuente, Jesús; Andía, Daniel; José Hernández, Juan; Fiol, Gabriel; Torné, Aureli
Abstract: Objective: The objective of this study was to analyse the temporal trend of HPV vaccination coverage (VC) in Spain in women aged 15‐55 years not included in systematic vaccination programmes during the period 2007‐2020. Methods: We assessed the vaccine coverage rate in this population based on three estimations: 1) annual vaccination coverage with at least one dose (VCR ≥ 1d), 2) annual VC for the full schedule (VCR3d), and 3) cumulative VC for the full schedule (aVCR). Results: Annual VCR ≥ 1d and VCR3d were highest in 2008 (2.40% and 0.66% respectively) and subsequently decreased drastically in 2011 (0.55% and 0.15%). From 2017 to 2019 there was an increase from 1.4‐fold to 1.6‐fold, respectively, which decreased in 2020. In relation to aVCR, there was an increasing trend throughout the study period with approximately 4.03% of the study population having been vaccinated against HPV in 2020. Conclusion: In Spain, the cumulative vaccination coverage against HPV in women between 15‐55 years old not included in current vaccination programmes remains very low. Nonetheless, the temporal trend has shown a slight increase in recent years. Despite the COVID‐19 pandemic in 2020, no significant negative impact on vaccination coverage has been observed in this population. Abstract : In Spain, cumulative vaccination coverage against HPV in women aged 15–55 years remains very low, but temporal trend has increased slightly in recent years.